Development and validation of a software tool for complex aircraft powertrains. (June 2016) - Donateo, T.; Ficarella, A.; Spedicato, L.
Highlights: A software for the designing and the backward analysis of aircraft powertrains. Map based modeling of powertrains components (in particular propeller and engine). Validation of the software with available data for a UAV. Power requirement and fuel consumption of the original powertrain (Wankel engine). Development of a high efficiency powertrain for the UAV (two-stroke Diesel engine). Abstract: A simulation software for the assessment of performance, costs and environmental impact of conventional and advanced configuration aircraft has been developed and validated. The software is named PLA.N.E.S. (PLAtform for New Environment-friendly Solutions), and includes a sizing routine and a mission simulator. The simulation is performed with the so-called backward paradigm, i.e. the flight conditions along the mission (altitude and speed versus time) are assumed to be known. Accordingly, the instantaneous power request of the aircraft to meet that flight mission and the corresponding instantaneous fuel consumption are calculated. In the case of advanced powertrains, it is also possible to choose different energy management strategies for the optimal control of the energy flows among engine, secondary equipment and storage systems during the mission. The components currently modeled in PLA.N.E.S. include energy converters (piston and Wankel engines, turboprop, fuel cell, etc.), energy storage systems (batteries, super-capacitors), auxiliaries and secondary power systems. The tool is designed to be integrated with a multi-objective optimization environment. In the present investigation PLA.N.E.S. has been applied to a Medium Altitude Medium Endurance (MAME) Unmanned Aerial Vehicle (UAV) as a case study to compare an experimentally validated Wankel-based powertrain with a proposed turbocharged diesel piston-prop system.